Multimodal functional imaging of prolonged neurological deficits in a patient suffering from familial hemiplegic migraine - Gutschalk, Alexander; Kollmar, Rainer; Mohr, Alexander; Henze, Marcus; Ille, Nicole; Schwaninger, Markus; Hartmann, Marius; Hähnel, Stefan; Haberkorn, Uwe; Rupp, André; Meyding-Lamadé, Uta (Neuroscience letters, 2002)
The case of a patient with familial hemiplegic migraine (FHM) suffering from prolonged right sided hemiparesis and aphasia that persisted for more than 10 days is reported. The symptoms were accompanied by slowing of the magnetoencephalogram over the left hemisphere, which normalized parallel to the clinical improvement. Positron emission tomography obtained on the 6th day revealed glucose-hypometabolism (hemispheric difference > or =10%) in left hemisphere's fronto-basal cortex, caudate nucleus, and thalamus. In contrast, magnetic resonance imaging including perfusion and diffusion weighted imaging was normal and did not show significant alterations of cortical perfusion or water mobility during the episode. We hypothesize that this finding provides evidence for a primary neuronal dysfunction causing the prolonged neurological deficits in FHM.
Gesehen am 25.10.2017